Multiscale modeling of process-induced residual deformation on carbon-fiber-reinforced plastic laminate from quantum calculation to laminate scale finite-element analysis. (July 2022) - Kawagoe, Yoshiaki; Kawai, Kenji; Kumagai, Yuta; Shirasu, Keiichi; Kikugawa, Gota; Okabe, Tomonaga
Abstract: Multiscale modeling, comprising quantum-chemical reaction path calculation, curing molecular dynamics (MD) simulation, microscopic finite-element analysis (FEA), and macroscopic FEA, was developed to predict the manufacturing-process-induced deformation of carbon-fiber-reinforced plastic (CFRP) laminates. In this approach, the thermomechanical properties, volumetric shrinkage due to the curing reaction, and gelation point of the matrix thermoset resin were evaluated using MD simulations coupled with quantum calculations. Homogenized orthotropic material properties and the cure-shrinkage strain of unidirectional (UD) lamina were then evaluated by microscopic FEA using the results of the MD simulations. Finally, process-induced deformation of the cross-ply laminate due to curing and thermal shrinkage was predicted by macroscopic FEA considering material and geometric nonlinearities, in which each layer of the laminate was modeled as a homogenized orthotropic body using the results of the microscopic FEA. The predictions made using the developed multiscale modeling agreed well with the results of the fabrication experiments in terms of the maximum deformation and the shape transition depending on the specimen dimensions. In addition, effects of the selection of matrix resin on process-induced behaviors, such as nanovoid nucleation in the matrix, residual stress, and deformation were investigated at each scale in detail. The results presented here provide important knowledge regarding the development of high-performance composite structures and for stable manufacturing. Highlights: Multiscale modeling was developed to predict process-induced deformation of CFRP. The modeling consists of a quantum calculation, MD simulation, and two-scale FEAs. The modeling reproduced well the deformations and shape transitions of experiments. The effect of resin type on deformation was clarified. The results contribute to the development of composite and its stable manufacturing.